Pop-up messages on electronic gaming machines in New Zealand: experiences and views of gamblers and venue staff. Issue 1 (2nd January 2016) - Landon, Jason; Palmer du Preez, Katie; Bellringer, Maria; Page, Alyssa; Abbott, Max
Abstract: In New Zealand, a pop-up message feature that interrupts gambling is mandatory on all electronic gaming machines (EGMs) in all venues. The present research documented the views and experiences of pop-up messages from a range of gamblers and gambling venue staff. A series of focus groups was held with 40 gamblers (ranging from infrequent gamblers to current/former problem gamblers), and 19 staff from casino and non-casino venues. Most participants thought that pop-up messages were ineffective as a harm-minimization measure. Venue staff participants viewed pop-up messages much more negatively than gamblers, who were generally accepting of their existence and sometimes described them as useful. Venue staff participants were also very negative about the additional hassles and confusion they believed to be caused by pop-up messages, and a range of problems they perceived with their accuracy. Nonetheless, there was a consistent although less prevalent view that pop-up messages were useful in reducing gambling harm and potentially bringing harmful gamblers to the attention of others. Participants raised some possibilities for enhancing their effectiveness; these were generally consistent with the evidence base developed since the introduction of pop-up messages in the New Zealand gambling environment.